A Socio-Pragmatic Analysis on Expressive Utterances in Action Movie and Its Translation - Tejaningrum, Ratna Adi (2012)
Education Muhammadiyah University of Surakarta. The aims of this research are to describe the equivalence of intention of expressive utterances in action film and its translation, and to describe the equivalence of politeness strategy of expressive utterances in action film and its translation. The type of this research is descriptive qualitative. The data source of this research is action film and its translation. The methods of analyzing data are observation and documentation. The techniques of analyzing data of this research are describing the equivalence of the intention by referring to the speech act theory and describing the equivalence of the politeness pattern by referring politeness strategy. Based on the result of the data analysis, the writer findsthe equivalence of the intentions and the equivalence of politeness pattern of expressive utterance in action film and its translation. The equivalece of intention of expressive utterance used in action film and its translation are: praising (22,22%), apologizing (13,89%), feeling of irritated (27, 78%), thanking (6,94%), accusing (4,17%), feeling of frightened (12,5%), feeling of surprised (2,78%) and feelingof pleasure (9,72%). The politeness pattern is divided into three kinds, they are: bald on record (45,83%), positive politeness (41,67%), and off record (12,5%).